Can Homeopathic Arsenic Remedy Combat Arsenic Poisoning in Humans Exposed to Groundwater Arsenic Contamination?: A Preliminary Report on First Human Trial. Issue 4 (2005) - Khuda-Bukhsh, Anisur Rahman; Pathak, Surajit; Guha, Bibhas; Karmakar, Susanta Roy; Das, Jayanta Kumar; Banerjee, Pathikrit; Biswas, Surjyo Jyoti; Mukherjee, Partha; Bhattacharjee, Nandini; Choudhury, Sandipan Chaki; Banerjee, Antara; Bhadra, Suman; et al.
Abstract : Groundwater arsenic (As) has affected millions of people globally distributed over 20 countries. In parts of West Bengal (India) and Bangladesh alone, over 100 million people are at risk, but supply of As-free water is grossly inadequate. Attempts to remove As by using orthodox medicines have mostly been unsuccessful. A potentized homeopathic remedy, Arsenicum Album-30, was administered to a group of As affected people and thereafter the As contents in their urine and blood were periodically determined. The activities of various toxicity marker enzymes and compounds in the blood, namely aspartate amino transferase, alanine amino transferase, acid phosphatase, alkaline phosphatase, lipid peroxidation and reduced glutathione, were also periodically monitored up to 3 months. The results are highly encouraging and suggest that the drug can alleviate As poisoning in humans.